Systemic regulation of mineral homeostasis by micro RNAs - Kehr, Julia (Frontiers in Plant Science, 2013)
Plants frequently have to cope with environments with sub-optimal mineral nutrient availability. Therefore they need to constantly sense changes of ion concentrations in their environment. Nutrient availabilities and needs have to be tightly coordinated between organs to ensure a balance between uptake and demand for metabolism, growth, reproduction, and defence reactions. To this end information about the nutrient status has to flow from cell-to-cell, but also between distant organs via the long-distance transport tubes to trigger adaptive responses. This systemic signalling between roots and shoots is required to maintain mineral nutrient homeostasis in the different organs under varying environmental conditions. Recent results begin to shed light on the molecular components of the complex long-distance signalling pathways and it has been proposed that systemic signals can be transported through the xylem as well as via the phloem. Several molecules, including nutrients, hormones, sugars, and small RNAs have been suggested to be involved in systemic communication over long distance (Liu et al. 2009). Recent research has suggested that in the case of mineral nutrients, the nutrients themselves, but also macromolecules like micro RNAs (miRNAs) can act as important information transmitters. The following review will summarise the current knowledge about phloem-mediated systemic signalling by miRNAs during ion nutrient allocation and adaptation to mineral nutrient deprivation, concentrating on the well-analysed responses to a lack of potassium, sulphur, and copper.